Los jueces y la política: ¿Imparcialidad/neutralidad versus compromiso democrático? - Brey Blanco, José Luis (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
This article analyses the relation between the judicial function and the political activity. It’s in three parts. The first part focuses on the description of the judges’s model of the 1978 Spanish Constitution. Regarding this subject, we came to the conclusion that the Magna Carta refuses both the idea of a kind of political judge and the opposite model, which would be that of a politically engaged judge. The second part is a theoretical reflection on the value of neutrality in application to the Judiciary, and the conclusion we came to is that this concept involves a positive reinforcement of the concept of impartiality, so we recommend this use. Finally, in the third part, we apply these conclusions to a particular case: the prohibition of the judges’s political activism (art. 127.1 Spanish Constitution).